PRELIMINARY ANALYSIS OF TEMPERATURE CHANGES DUE TO SYNOPTIC SCALE DISTURBANCES AT SYOWA STATION, ANTARCTICA IN WINTER - ナイトウ, ノゾム; ムラマツ, ヒサフミ; NAITO, Nozomu; MURAMATSU, Hisafumi (National Institute of Polar Research, 1996)
P(論文) The Antarctic surface air temperature often increases severely in winter when a synoptic scale disturbance comes close and then decreases after it goes away. The mechanism of these temperature changes in analyzed from the data observed at Syowa Station, Antarctica in 1993 by the 34th Japanese Antarctic Research Expedition (JARE-34). For this purpose, fifteen cases each are selected for both the prominent warming and the succeeding cooling events in winter. The magnitude of changes in temperature due to destruction or reformation of the surface temperature inversion during the events is estimated from comparison of the vertical temperature profiles above Syowa Station before and after each events. Its contribution amounts to about half of the observed change in the surface temperature.The horizontal advection of sensible heat is calculated from the thermal wind shear relation. It is shown that the horizontal advection of warm and cold air are observed in the warming and the cooling events, respectively. It is estimated from the average heat budget that there should be an upward current of 0.2 to 0.8 (cms)^<-1> during the warming events and a downward current of less than 0.4 (cms)^<-1> during the cooling events in the 850 to 300 hPa layer. departmental bulletin paper